A quick approach for rheological evaluation of warm asphalt binders using response surface method - Hamzah, Meor Othman; Golchin, Babak; Woodward, David (Journal of Civil Engineering and Management, 2017)
This paper describes a quick approach for quantification of the effects of a chemical warm named Rediset, and its interactions with temperature and aging on the rheological properties of asphalt binders using Response Sur-face Method. The central composite method was applied to design experimental programs for three test temperature conditions, namely; very high temperature (120–180 °C), high temperature (46–82 °C), and intermediate temperature (19–31 °C). Rotational viscosity, G*/sin δ and G*sin δ were selected as parameters to assess the effects of the chemical warm additive on the rheological properties of asphalt binders for different aging conditions. Evaluation of the effects of this additive on the transformed value of G*/sin δ at high temperatures indicates that additive content has significant effect on Ln(G*/sin δ). The results for intermediate temperatures show that this additive has a positive effect on G*sin δ of asphalt binders.